2021
DOI: 10.3390/land10050449
|View full text |Cite
|
Sign up to set email alerts
|

Model Prediction of the Soil Moisture Regime and Soil Nutrient Regime Based on DEM-Derived Topo-Hydrologic Variables for Mapping Ecosites

Abstract: Ecosites are required for stand-level forest management and can be determined within a two-dimensional edatopic grid with soil nutrient regimes (SNRs) and soil moisture regimes (SMRs) as coordinates. A new modeling method is introduced in this study to map high-resolution SNR and SMR and then to design ecosites in Nova Scotia, Canada. Using coarse-resolution soil maps and nine topo-hydrologic variables derived from high-resolution digital elevation model (DEM) data as model inputs, 511 artificial neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The MⅣ mode was slightly worse than the MⅤ mode, with a higher RMSE value but a slightly higher R value In densely vegetated areas, the radar signal may not reach the soil through the plant canopies, resulting in less accurate estimation of SM. Some studies have shown that, the C-band radar signal is insensitive to SM when NDVI > 0.7 [48][49][50].…”
Section: B Evaluation and Comparison Of Scenarios And Different Combi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The MⅣ mode was slightly worse than the MⅤ mode, with a higher RMSE value but a slightly higher R value In densely vegetated areas, the radar signal may not reach the soil through the plant canopies, resulting in less accurate estimation of SM. Some studies have shown that, the C-band radar signal is insensitive to SM when NDVI > 0.7 [48][49][50].…”
Section: B Evaluation and Comparison Of Scenarios And Different Combi...mentioning
confidence: 99%
“…Therefore, in this section, we reanalyze the different sensitivity of C-band to soil when NDVI is in different range. First, we divided the range of measured SM (2 to 40 vol.%), which we divided into two parts: dry to slightly moist (0 ~ 25 vol.%), based on experience; and very wet (25 ~ 40 vol.%) [48]. Second, we perform inversion analysis in different NDVI ranges using four methods.…”
Section: B Evaluation and Comparison Of Scenarios And Different Combi...mentioning
confidence: 99%